Increasing the Quality of Budget Information for Implementing Policies Regarding Programs Academic at Home Private Junior High School, Tobasa - Cawir Refinus Purba; Saut Purba (Budapest International Research and Critics University, 2023)
Budget Management in Improving the Quality of Budget Information is needed, so that the desired goals can be achieved effectively and efficiently. The purpose of this research is to find out the stages of budget planning in improving the quality of information at Rumah Harapan Tobasa private junior high school, how the mechanism of implementation and distribution of the budget used at Rumah Harapan Tobasa private junior high school and how budget supervision in improving the quality of information at Rumah Harapan Tobasa private junior high school. This type of research uses descriptive qualitative methods and research methods using literature studies. The results showed that the budgeting stages carried out by the school of Rumah Harapan Tobasa Private Junior High School have not been able to improve the quality of budget information to carry out policies regarding academic programs, so that the funding needs of school activities can be planned, procured, recorded transparently, and used to finance the implementation of school academic program policies effectively and efficiently. Carry out direct budget supervision, by checking directly both on programs that have been implemented and checking budget information once a month.